Animated Video Development Using Macromedia Flash for Arabic Vocabulary Recognition in Early Childhood Education - Nurlaila, Nurlaila; Husni, Suci Nisaul; Warmansyah, Jhoni; Sari, Meliana; Yuningsih, Restu; Trimelia Utami, Winda (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
The recognition of Arabic vocabulary in early childhood education is a vital component in fostering foundational language skills, yet remains constrained by limited access to effective learning media. This study aims to develop animated video media using the Macromedia Flash application to support Arabic vocabulary acquisition among early learners in preschool settings. Utilizing a research and development approach with a modified 4-D modelÔÇöfocusing on the define, design, and develop stagesÔÇöthe study employed expert validation sheets and teacher response questionnaires to evaluate the mediaÔÇÖs validity and practicality. The animated video, themed around school equipment, was designed to promote vocabulary learning through engaging visual narratives. The media attained a high validity score of 89.33% in terms of construct, content, and language, and a 90% practicality rating from educators, indicating its relevance and applicability in classroom contexts. These findings affirm that the developed animated video is both valid and practical, offering a promising tool for enhancing Arabic vocabulary instruction in early childhood education.┬á┬á